Makna Hospitality Bagi Karyawan Front Office: Pendekatan Fenomenologi - Ni Putu Helda Silpia Apriyani (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
This study aims to explore the meaning of hospitality as experienced by front office employees of five-star hotels in South Kuta, Bali, using a phenomenological approach. As the frontline in guest interactions, the subjective experience of employees significantly influences service quality, guest satisfaction, and the hotel's image. Data collection was carried out through semi-structured interviews with 18 informants, observation, and internal documentation. Data analysis followed a descriptive phenomenological procedure to produce rich contextual descriptions. The findings indicate that hospitality for front office employees is complex and influenced by both internal and external factors, including professional identity, emotional labor, and the quality of interpersonal relations with guests. Although existing theoretical frameworks are relevant, there are gaps between theory and practice in stress management and the effectiveness of compensation. Recommendations include the development of emotional training programs, non-financial rewards, and employee involvement in job redesign and retention strategies based on competence development. These strategies are expected to improve job satisfaction, service quality, and guest loyalty.